A single copy of SecYEG is sufficient for preprotein translocation - Kedrov, Alexej (Nature Publishing Group, 2011)
The heterotrimeric SecYEG complex comprises a protein-conducting channel in the bacterial cytoplasmic membrane. SecYEG functions together with the motor protein SecA in preprotein translocation. Here, we have addressed the functional oligomeric state of SecYEG when actively engaged in preprotein translocation. We reconstituted functional SecYEG complexes labelled with fluorescent markers into giant unilamellar vesicles at a natively low density. Förster's resonance energy transfer and fluorescence (cross-) correlation spectroscopy with single-molecule sensitivity allowed for independent observations of the SecYEG and preprotein dynamics, as well as complex formation. In the presence of ATP and SecA up to 80% of the SecYEG complexes were loaded with a preprotein translocation intermediate. Neither the interaction with SecA nor preprotein translocation resulted in the formation of SecYEG oligomers, whereas such oligomers can be detected when enforced by crosslinking. These data imply that the SecYEG monomer is sufficient to form a functional translocon in the lipid membrane.